2012
DOI: 10.1186/2191-219x-2-37
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of 2-chloro N-[(S)-{(S)-1-[11 C]methylpiperidin-2-yl} (phenyl)methyl]3-trifluoromethyl-benzamide ([11 C]N-methyl-SSR504734) as a PET radioligand for glycine transporter 1

Abstract: BackgroundDysfunction of the glycine transporter 1 (GlyT1) has been suggested to be involved in psychiatric disorders such as schizophrenia. GlyT1 inhibitors have therefore been considered to have antipsychotic therapeutic potential. Positron emission tomography (PET) imaging probes for GlyT1 are, consequently, expected to be useful for investigating the mechanism of such disease conditions and for measuring occupancy of GlyT1 inhibitors in vivo. The aim of this study was to assess the potential of 2-chloro N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…With regard to the lack of changes in thalamus, it is interesting to note that a previous PET study in non-human primates with the GlyT1 ligand N-[ 11 C]methyl-SSR504734 also found that this region behaves differently from other brain regions, which was proposed to be due to a different GlyT1 occupancy or a different non-displaceable component. 67 In addition to the minor decrease of radioactivity between early and late measurements, the TACs for cerebral cortex showed a more pronounced decline during the late measurement that started roughly 200 min after tracer administration and that was not observed in cerebellum and midbrain (Figure 2F), supporting previous evidence for a reduced residence time of ALX5407 in forebrain compared to caudal brain regions. 22 Finally, it should be noted that in contrast to the prominent binding of [ 18 F]ALX5407 to the corpus callosum observed in our in vitro experiments (Figure 1), there was little accumulation of radioactivity in this tract during the μPET measurements with [ 18 F]ALX5406 (Figure 2D,E).…”
Section: ■ Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…With regard to the lack of changes in thalamus, it is interesting to note that a previous PET study in non-human primates with the GlyT1 ligand N-[ 11 C]methyl-SSR504734 also found that this region behaves differently from other brain regions, which was proposed to be due to a different GlyT1 occupancy or a different non-displaceable component. 67 In addition to the minor decrease of radioactivity between early and late measurements, the TACs for cerebral cortex showed a more pronounced decline during the late measurement that started roughly 200 min after tracer administration and that was not observed in cerebellum and midbrain (Figure 2F), supporting previous evidence for a reduced residence time of ALX5407 in forebrain compared to caudal brain regions. 22 Finally, it should be noted that in contrast to the prominent binding of [ 18 F]ALX5407 to the corpus callosum observed in our in vitro experiments (Figure 1), there was little accumulation of radioactivity in this tract during the μPET measurements with [ 18 F]ALX5406 (Figure 2D,E).…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…As can be seen by close inspection of the early and late measurements with [ 18 F]­ALX5406 (Figure F), radioactivity in all brain regions except for the thalamus decreased somewhat between the two successive μPET measurements, which could reflect clearance of small amounts of unconverted methyl ester or unbound [ 18 F]­ALX5407 from brain. With regard to the lack of changes in thalamus, it is interesting to note that a previous PET study in non-human primates with the GlyT1 ligand N -[ 11 C]­methyl-SSR504734 also found that this region behaves differently from other brain regions, which was proposed to be due to a different GlyT1 occupancy or a different non-displaceable component . In addition to the minor decrease of radioactivity between early and late measurements, the TACs for cerebral cortex showed a more pronounced decline during the late measurement that started roughly 200 min after tracer administration and that was not observed in cerebellum and midbrain (Figure F), supporting previous evidence for a reduced residence time of ALX5407 in forebrain compared to caudal brain regions .…”
Section: Resultsmentioning
confidence: 88%
“…We analyzed the 24 remaining published reports that consisted of 104 sets of data. In seven cases, the authors submitted data (8,(17)(18)(19)(20)(21)(22), and for the remaining 17 reports, we extracted the data from published graphs with GetData Graph Digitizer digitization software (11,13,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The characterization of the data in terms of species, sex, age, drug, dose, and other identifiers is presented in Table 1.…”
Section: Linear Regressions Of Published Datamentioning
confidence: 99%
“…Among these GlyT1 specific PET radioligands, [ 11 C]GSK931145, [ 18 F]MK‐6577, and [ 11 C]RO5013853 have shown promise in preclinical and clinical evaluations (Gunn et al, ; Joshi et al, ; Wong et al, ). Others, such as [ 11 C] N ‐methyl‐SSR504734 and [ 11 C]SA1, have also demonstrated their potential in imaging GlyT1 in nonhuman primates (Fuchigami et al, ; Toyohara et al, ).…”
Section: Introductionmentioning
confidence: 99%